Pengelolaan Kecemasan dengan Terapi Murottal Al-Qur'an Pada Pasien Hemodialisis di RSUD Pandan Arang Boyolali - Rachman, Tri Martiani; Maksum, Maksum (Universitas Pahlawan Tuanku Tambusai, 2025)
Anxiety is a common psychological issue among hemodialysis patients, often caused by invasive and repetitive therapies. Approximately 38–45% of hemodialysis patients experience moderate to severe anxiety, which can disrupt their quality of life. This study aims to explore the effectiveness of Qur'anic murottal therapy in managing anxiety among hemodialysis patients at RSUD Pandan Arang Boyolali. The method used is a qualitative case study involving a 59-year-old patient undergoing hemodialysis and experiencing anxiety. The murottal therapy intervention was conducted over three consecutive days, with each session lasting approximately 15 minutes. The results of the study indicate a reduction in anxiety scores from 23 to 15, as well as improvements in the patient's vital signs, including blood pressure and respiratory rate. The patient reported feeling calmer and improved sleep quality. Qur'anic murottal therapy has proven to be an effective non-pharmacological intervention for managing anxiety in hemodialysis patients. Education and support from healthcare professionals are essential to optimize the implementation of this therapy.